sTREM2 cerebrospinal fluid levels are a potential biomarker for microglia activity in early‐stage Alzheimer's disease and associate with neuronal injury markers - Marc Suárez‐Calvet; Gernot Kleinberger; Miguel Ángel Araque Caballero; Matthias Brendel; Axel Rominger; Daniel Alcolea; Juan Fortea; Alberto Lleó; Rafael Blesa; Juan Domingo Gispert; Raquel Sánchez‐Valle; Anna Antonell; et al. (EMBO Molecular Medicine)
Abstract TREM2 is an innate immune receptor expressed on the surface of microglia. Loss‐of‐function mutations of TREM2 are associated with increased risk of Alzheimer's disease (AD). TREM2 is a type‐1 protein with an ectodomain that is proteolytically cleaved and released into the extracellular space as a soluble variant (sTREM2), which can be measured in the cerebrospinal fluid (CSF). In this cross‐sectional multicenter study, we investigated whether CSF levels of sTREM2 are changed during the clinical course of AD, and in cognitively normal individuals with suspected non‐AD pathology (SNAP). CSF sTREM2 levels were higher in mild cognitive impairment due to AD than in all other AD groups and controls. SNAP individuals also had significantly increased CSF sTREM2 compared to controls. Moreover, increased CSF sTREM2 levels were associated with higher CSF total tau and phospho‐tau181P, which are markers of neuronal degeneration and tau pathology. Our data demonstrate that CSF sTREM2 levels are increased in the early symptomatic phase of AD, probably reflecting a corresponding change of the microglia activation status in response to neuronal degeneration.